Dream snow - Carle, Eric (New York : Philiomel Books, 2000)
In this musical and sound effects book, a farmer celebrates Christmas after the first snowfall.
Keywords: Christmas -- Fiction; Snow -- Fiction; Farm life -- Fiction; Sound effect books; Musical books; Toy and movable books